Orofacial Pain Biomarkers - Goulet, Jean-Paul; Velly, Ana Miriam (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book provides up-to-date information on all aspects of orofacial pain biomarkers. It opens by presenting background information on clinical phenotypes and the neurobiological substrates underlying chronic orofacial pain and by explaining the potential role of biomarkers in the diagnosis, prognostic evaluation, and treatment of orofacial pain. The main section of the book examines the contribution of human and animal studies to the field of biomarkers for orofacial pain and discusses biomarkers for masticatory muscle pain, temporomandibular joint pain, neuropathic face pain, and autonomic nervous system involvement in trigeminal facial pain. The potential impacts of the immune system on orofacial pain biomarkers and candidate gene phenotypes with possible links to chronic orofacial pain conditions are also addressed, and differences and similarities between saliva and serum biomarkers for pain are explained as well. The final section covers research-related issues in assessment methods and statistical analyses used in evaluating biomarkers, identifies future challenges and suggests new directions in the field.
Keywords: Dentistry.; Pain medicine.; Oral surgery.; Maxillofacial surgery.; elektronické knihy; electronic books